Separation of nadolol racemates by high pH reversed-phase fixed-bed and simulated moving bed chromatography - Arafah, Rami (2023)
The separation of nadolol racemates under high pH reversed-phase using both the fixed-bed (FB) and the simulated moving bed (SMB) preparative chromatographic techniques is reported after the previous published work [1] where the Waters XBridge C18 adsorbent and an ethanol:water:diethylamine solvent mixture were validated to allow the separation of the multicomponent feed mixture composed by four nadolol stereoisomers into two pure racemates (two pairs of enantiomers). In this work, the experimental preparative separations using one commercial fixed-bed preparative HPLC Azura system equipped with one sole column of preparative dimensions (30 mm ID × 250 mm L) and one labscale SMB apparatus (the FlexSMB-LSRE pilot unit) equipped with six semi-preparative columns (19 mm ID × 100 mm L) are presented. Both systems use the Waters XBridge C18 adsorbent of 10 μm particle diameter. The screening of the mobile phase composition elected the 30:70:0.1 (v/v/v) ethanol:water:diethylamine solvent mixture to perform both FB and SMB preparative operations. A large set of experimental, modelling and simulation results are presented, including pulses, measurement and modelling of the adsorption equilibrium isotherms, and its validation through breakthroughs measurements. The modelling and simulation steps allowed the prediction and the optimization of both the FB and SMB operating conditions. For FB, using a feed concentration of 9 g/L of an equimolar mixture of the two nadolol racemates, both were recovered almost pure (at least 99.9 %), with a global system productivity of 3.06 gfeed/(Lbed.hr) and a solvent consumption of 4.21 Lsolvent/gfeed. For SMB, the pilot unit’s pressure drops limits imposed a maximum internal flow-rate of only 5 mL/min and, for a nadolol feed concentration of 2 g/L, both racemates were recovered 100 % pure, with a system productivity of 0.13 gfeed/(Lbed.hr) and a solvent consumption of 6.19 Lsolvent/gfeed. Additional simulation results showed that a SMB preparative unit can perform the 9 g/L nadolol racemate separation with a system productivity of 3.61 gfeed/(Lbed.hr) and a solvent consumption of only 1.95 Lsolvent/gfeed using the same average internal flow-rate as in FB operation. Even better SMB productivities can still be obtained using the same feed or solvent flow-rates as in FB operation if the internal SMB flow-rates are allowed and not limited by the system pressure drop. The experimental results presented in this work validate the strategy of separating a four nadolol stereoisomers mixture into two pure nadolol racemates, each one composed by a pair of nadolol enantiomers, using an achiral C18 adsorbent through FB and SMB chromatographic techniques. Each nadolol racemate can later be purified into pure nadolol stereoisomers using standard binary chiral FB and SMB chromatography. In this way, this works introduces a real and experimental solution for the complete multicomponent preparative separation of the four nadolol stereoisomers.